2011
DOI: 10.1002/jbm.b.31814
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical, histological and ultrastructural analyses of laser micro‐ and nano‐structured titanium implant after 6 months in rabbit

Abstract: Short-term, experimental studies of partly laser-modified implants with nano-scale surface topographical features have recently shown a considerable increase in the biomechanical anchorage to bone. The aim of this study is to evaluate the biomechanical and bone-bonding ability of partly laser-modified implants compared with machined implants after a healing period of 6 months in a rabbit model. The results showed a 170% increase in removal torque. Histology and scanning electron microscopy demonstrated osseoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 32 publications
5
45
0
1
Order By: Relevance
“…Such results are likely due to the higher surface roughness and thereby mechanical interlocking between bone and laser-sintered/ textured implants compared to implants that are first machined and then textured by a variety of methods (Coelho et al 2008). Other studies have also shown acceptable osseointegration of laser-treated surfaces [8,13]. Since previous work has reported the appropriate biocompatible and osseoconductive properties of laser-treated and laser-sintered implants, the present study aimed to investigate whether laser-sintered fabricated implants would present different reliability and failure modes compared to current industry standard alumina-blasted/acid-etched implant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Such results are likely due to the higher surface roughness and thereby mechanical interlocking between bone and laser-sintered/ textured implants compared to implants that are first machined and then textured by a variety of methods (Coelho et al 2008). Other studies have also shown acceptable osseointegration of laser-treated surfaces [8,13]. Since previous work has reported the appropriate biocompatible and osseoconductive properties of laser-treated and laser-sintered implants, the present study aimed to investigate whether laser-sintered fabricated implants would present different reliability and failure modes compared to current industry standard alumina-blasted/acid-etched implant.…”
Section: Discussionmentioning
confidence: 95%
“…Transmission electron microscopy and chemical analysis showed coalescence between mineralized tissue and the surface of the lasermodified implant [13]. Recently, improved biomechanical response has been reported for laser-sintered compared to alumina-blasted/acid-etched implants at early times (1 and 6 weeks in vivo) [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This oxide layer can further be modified to enhance bone bonding by altering its surface topography. Both micro and nanostructured surfaces have been shown to improve bone growth and cellular activity on the surface of titanium [58][59][60]. In work with our collaborators, laser modification of a titanium screw (Biohelix, Brånemark Integration AB, Sweden) has resulted in a titanium dioxide surface with a unique nanotopography (figure 4a) [58].…”
Section: (B) Titanium-bone Interfacementioning
confidence: 99%
“…34 The fact that nanostructured surfaces promoted long-term bone bonding and interface strength in vivo, as determined by coalescence between mineralized bone and the nanostructured surface and a substantial increase in removal torque, is of clinical importance. 35 Furthermore, a previous in vivo study of electropolished titanium implants with nanosized hydroxyapatite particle modification compared with a non-coated control showed greater bone contact for the modified surface after 4 weeks of healing. 36 Acid-etched microtopography with irregular, discrete, 20-40 nm hydroxyapatite particles has also been reported to enhance the strength and direct bone bonding of osseointegration.…”
mentioning
confidence: 92%